Cover Fuel Cells 4/2017. Issue 4 (August 2017) - Unknown
Abstract : The European Fuel Cells Forum (EFCF), founded by Ulf Bossel in 1994, is now continued by the EUROPEAN FUEL CELL FORUM AG (www.EFCF.com ), founded by Olivier Bucheli and Michael Spirig, and has become an internationally recognized and appreciated conference series. In the framework of the conference series this Special Issue EFCF2016 covers the 12 th European SOFC & SOE Forum 2016, held July 5–8, 2016 in Lucerne, Switzerland (Chairman Prof. Nigel Brandon, Imperial College, United Kingdom). The conference focused on solid oxide fuel cells and electrolyzers, with the first time addition of a new category addressing reactors and separators based on solid oxide membranes.